KUMUK TÜRKÇESİ GRAMERİ - BAYKOCA, AHMET NACİ (Fırat Üniveristesi, 1998)
Kıanıık Türkçe'si (îramcrı SUM.MURY MASTERS THESIS TUK C;KAMMKR OK KIIMUK TURKISH Ahmet Naci Bay koca KIRAT İINİVKRSİTESİ Sosyal Bilimler Enstitüsü Türk Dili Anabilim Dalı 1998 Sayfa 255 The most ol" Kumuks which is orijanated from Turkish racial, are living Autonomy Republic of Dagestan, dependant to Fedaration of Russia. Other Kumuks are living in Turkey, North Osetia and Chechenia partly. According to census, 1992, there are 282.000 Kumuks in Dagestan. This population was third ethnic group in Dagestan. The Kumuks are the remaing part of Turks, placed to that region after establishing of Hazer state, lived long time as a colony of Hazars, Altmordu State and Ottoman Empire respectively and also they established several limes their own state. XIVKııımık Türkçe'si iirumen Kumuks were dependant tu Union of Soviet Socialist Republics from 1917 to 1990. Then they declared the freedom of Kumuks after breaking down of USSR. Nowadays, Kumuks are living under the Autonomy Republic of Dagestan, dependant to Federation of Russia and they have a strong effect on North Cauasus. The concil of United Caucasus, gathered in 1917, accepeld the Kumuk Turkish as common language of Caucasus peopels. The most important property of Kumuk Turkish, distinguished from other Turkish accents is to carry the Kipchak Turkish and Oğuz Turkish characteristics. Because of this characteristics, the language historicans have a difficulties for classifastion. In this study, we've tried togive the grammar of Kumuk Turkish comparatively. So, we've thought that it is neccesary to slady on dctcrminction of the origin of Kumuk Turkish. The main result of this study is that the Kumuk Turkish is an regional accent of Kipchak Turkish and effected from Mongol, Arabic, Persian, Oguz Turkish and other Caucasus Languages. XV
The Grammer of Kumuk Turkish
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature